Low to medium-low risk perception for dengue, chikungunya and Zika outbreaks by infectious diseases physicians in France, Western Europe - Marion Le Tyrant; Daniel Bley; Catherine Leport; Serge Alfandari; Jean-François Guégan (BMC, 2019)
Abstract Background Many tropical countries are currently experiencing dengue (DEN), chikungunya (CHIK) and also more recently Zika (ZIKA) epidemics (particularly in Latin America). Although the risk of transmission and spread of these infections in temperate regions remains a controversial issue, vector-borne diseases have been widely reported in the media and have been the focus of preventive strategies by national and international policy-makers and public health authorities. In this context, we wanted to determine the extent of risk perception in infectious diseases (ID) physicians of the current and future risk of arboviral disease introduction, autochthonous case development and epidemic scenarios in France, Western Europe. Methods To this aim, we developed an original standardized questionnaire survey which was disseminated by the French Infectious Diseases Society to ID physician members. Results We found that ID physicians perceived the risk of introduction and outbreak development of DEN, CHIK and ZIKA in France to be low to medium-low. Generalized Linear Model(s) identified medical school training, the extent of professional experience, and awareness of the French national plan regarding arboviral infections as significant predictors for lower risk perception among respondents. Conclusion Despite the fact that arboviral diseases are increasingly being imported into France, sometimes resulting in sporadic autochtonous transmission, French ID physicians do not perceive the risk as high. Better communication and education targeting health professionals and citizens will be needed to enhance the effectiveness of the French national plan to prepare against arboviral diseases.